2017
DOI: 10.1016/j.nicl.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral prefrontal cortex contributes to the impaired behavioral adaptation in alcohol dependence

Abstract: Substance-dependent individuals often lack the ability to adjust decisions flexibly in response to the changes in reward contingencies. Prediction errors (PEs) are thought to mediate flexible decision-making by updating the reward values associated with available actions. In this study, we explored whether the neurobiological correlates of PEs are altered in alcohol dependence. Behavioral, and functional magnetic resonance imaging (fMRI) data were simultaneously acquired from 34 abstinent alcohol-dependent pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 113 publications
(160 reference statements)
4
31
1
1
Order By: Relevance
“…In this case, what should be an easy decision perhaps more obvious to others is approached similar to a difficult decision. These findings are consistent with previous observations that AD show reduced discrimination of conflict (Beylergil et al, 2017) and risk levels (Zhu et al, 2016) with reported conflict-related deficits in dorso-lateral prefrontal cortex(DLPFC) (Boschin et al, 2016;Beylergil et al, 2017). In humans, the rate of evidence accumulation or the drift rate has been linked to the fronto-parietal network (Mulder et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In this case, what should be an easy decision perhaps more obvious to others is approached similar to a difficult decision. These findings are consistent with previous observations that AD show reduced discrimination of conflict (Beylergil et al, 2017) and risk levels (Zhu et al, 2016) with reported conflict-related deficits in dorso-lateral prefrontal cortex(DLPFC) (Boschin et al, 2016;Beylergil et al, 2017). In humans, the rate of evidence accumulation or the drift rate has been linked to the fronto-parietal network (Mulder et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Other shared dysfunctions include impaired self-control (e.g. reduced top-down, inhibitory control); linked to dysfunction in frontal-subcortical brain circuits ascribed to decision-making and goal-directed behaviour [22][23][24][25][26][27][28][29][30][31] which limit recovery [32][33][34][35][36]. While there may not be a single phenotype, or set of related neural processes, that confers vulnerability to addictions, impairment in these reward, stress and control-related processes may shape various pathways in and out of the addiction cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that individuals with AUD have difficulties in adapting their responses to the changing contingencies of reward-guided decision-making. Weaker activity in the bilateral DLPFC and the dorsal anterior cingulate, associated with loss of adaptive control of action selection, could be linked with cognitive inflexibility when reinforcement contingencies change [ 42 ]. In Wrase and colleagues [ 19 ], individuals with AUD showed weaker sensitivity in the putamen and in the caudate head during the anticipation of monetary gain.…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholic brain damage seems to be partially reversible in some cases, although organic brain damage often remains permanent [ 40 , 41 ]. The neuropsychological consequences of AUD inevitably include a reduced control of behavior and the suppression of psychosocial adaptability skills [ 42 ]. Patients with AUD were found to show higher levels of impulsive choice than controls in a delay discounting task; also, higher delay discounting rates were markedly correlated with greater impulsivity trait scores [ 43 ].…”
Section: Neuropsychological Features Of Gd and Audmentioning
confidence: 99%